Who is the manager actually? (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article talks about the style of what it means to work in a specific way in management. There are parts of the style that are being carried out in the name of the management style, style of work, style of work of the leader.The manager of cultural and art institutions has repeatedly put forward his views on his style by foreign and domestic scientists. The specific and invariable methods used by the controller in the control process ,the set of actions indicates the control style. The presence of each leader's own style of work is evident in the current activities.